INCLUSIVE GROWTH OR RISING GAPS? A MACROECONOMIC PERSPECTIVE ON ASEAN INCOME INEQUALITY - Roseziahazni Abdul Ghani; Zuraida Mohamad; Noorhayati Yusof Ali; Zuriyati Ahmad; Ira Mazliana Mhd Atan (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
This study explores the evolving landscape of income inequality across five key ASEAN nations comprising Indonesia, Malaysia, the Philippines, Singapore, and Thailand from 1990 to 2022. Using the Gini coefficient and a static panel data approach, the research investigates how major macroeconomic forces shape income distribution. The analysis reveals that increased government spending and lower inflation are powerful tools in narrowing income gaps. In contrast, rising agricultural value-added, greater female labor force participation, and expanded arable land are linked to widening disparities. Interestingly, unemployment growth and foreign direct investment (FDI) show no significant impact on inequality levels. These findings highlight the multifaceted nature of economic inequality and call for nuanced, evidence-based policy responses. To build a more inclusive future, ASEAN policymakers must prioritize strategic fiscal management, inflation control, and labor market reforms tailored to their unique national contexts.